(untitled) (Orthodontic Journal of Nepal, 2015)
According to an opinion poll doctors topped the list among various professionals whom the public believe the most in telling truth; while journalists were on the bottom of the list. The MORI poll carried on behalf of British Medical Association showed that 87% believe doctors don’t lie, while 85% assume journalists don’t report truth. Surfacing amidst the trust bestowed upon the doctors and mistrust for the journalists, this article attempts to explain various aspects of dental journalism.